An Overview of Tuberculosis Chemotherapy - A Literature Review - Sarangi, Manoj Kumar; Padhi, Sasmita (Journal of Applied Pharmaceutical Research, 2016)
Tuberculosis (TB) is a major global health threat. The emergence of human immunodeficiency virus (HIV) and also multi drug resistant (MDR) and extremely drug resistant (XDR)-TB poses a vital challenge to the control of the disease. For the last 50 years, no new anti-TB drug has been discovered. This literature review provides a brief discussion of existing drugs and emerging drug targets, and also of the advantages of incorporating modern drug delivery systems and immune modulators in order to improve the existing treatment regimen in terms of better efficacy, reduced drug administration frequency, shortened period of treatment and reduced drug related toxicity. The investigation for a new drug target is essential to continue the battle against MDR and XDR-TB. However, owing to the enormous cost and time involved in new drug development, improvement of the existing treatment regimen is seen to be a valid alternative.Ã Ã